PROGNOSTIC SIGNIFICANCE OF SERUM BILIRUBIN IN STROKE - Arsalan, Arsalan; Ismail, Muhammad; Khattak, Muhammad Bilal; Khan, Faramoz; Anwar, Muhammad Jalil; Murtaza, Zeeshan; Khan, Abuzar (Journal of Ayub Medical College Abbottabad, 2011)
Background: Oxidative injury is an important cause of the neurologic lesion in stroke. Serum bilirubin is considered a natural antioxidant that may affect the prognosis of stroke. The purpose of this study was to evaluate the prognostic significance of bilirubin in stroke patients. Methods: A prospective cross-sectional study was conducted in Medical Units of Khyber Teaching Hospital, Peshawar. Inpatients admitted with acute attack of stroke were included in this study. Data regarding serum bilirubin and concurrent cerebrovascular risk factors were collected. National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS) were used to analyse stroke's severity and functional outcomes, respectively. Results: Hypertension, diabetes mellitus and heart diseases were the most common risk factors. Patients were divided into 3 groups on the basis of serum bilirubin, i.e., ‰¤0.6 mg/dl (Group-1), 0.7-0.9 mg/dl (Group-2), and ‰¥1.0 mg/dl (Group-3). The mean pre-hospitalisation NIHSS score for Groups 1, 2 and 3 was 5.62, 11.66 and 25.33, respectively; and post-hospitalisation score was 0.875, 3.76 and 16.26, respectively. The pre-hospitalisation mRS score was 4 for Group-1, 4.52 for Group-2 and 4.93 for Group-3; while post-hospitalisation Mrs Score was 1.50, 2.38 and 4.26, respectively. Average serum bilirubin level was significantly higher in patients with poor outcomes as compared with good outcomes (p<0.01). Conclusions: This study suggests that higher serum bilirubin levels were associated with increased stroke severity, longer hospitalisation and poor prognosis. Keywords: Stroke severity, stroke outcome, stroke prognosis, serum bilirubin, National Institutes of Health Stroke Scale (NIHSS), modified Rankin Scale (mRS)